Pelatihan Pembuatan Media Pembelajaran Interaktif Bagi Guru Smp Negeri 3 Topos - Yul, Fadlul Amdhi; Siska, Jumiati; Mesterjon; Afif , Ahmad (Jurnal Kewirausahaan dan Bisnis, 2019)
The objectives of this service are to: (1) Help teachers to be able to utilize the Lectora application program and, (2) Be able to produce media works and IT-based learning evaluations (Lectora) in schools to help achieve learning objectives. Meanwhile, the benefit is to improve teachers' ability to create learning media using the Lectora application program and be able to make it independently. The community service program in the form of training was held on 28-29 August and was attended by 18 class teachers, principals and employees of SMP N 3 Topos. It was held from 10:30 am to 1:30 pm. The method of implementation of this training is lecture, demonstration, practicum, question and answer and evaluation. The materials used in this training are laptop, Lectora application, LCD Projector, and audio speakers. The results achieved in this training are: (1) SMPN 3 Topos teachers who have participated in the training on making learning media and have been able to make a simple interactive learning media and evaluation based on Lectora, and (2) the community service program in the form of training on making Lectora-based learning media has run as planned and reached the target participants, namely all 18 class teachers of SMP N Topos.